Perancangan Interior Boutique U.S. House of Design di Surabaya - Yusita Kusumarini, Indah Ariyani (Intra, 2014)
Fashion is not simple term to describe clothes but a lifestyle pursued in the society of big cities. Itâs an outcome of the non-stop development of the international brand clothing lines. Local brand clothing lines are on the move as well, ready to compete with the international brand fashion. U.S. House of Design is one of the local brand fashion with high quality fashion which participated the fashion competition since July 2012. For it is able to win the heart of the society, it has to have a strong brand image. The brand image is including the interior branding that is going to be the retail house for the high fashion produced by U.S. House of Design.